Analisis Kontribusi Pertumbuhan Armada terhadap Peningkatan Pendapatan PT XYZ Samudera Cabang Merak dengan Pendekatan SEM-PLS - Agung Kwartama; Yanto Rusmanto (JURNAL TRANSMA, 2026)
This study aims to quantitatively analyze the contribution of fleet growth to the revenue increase of PT XYZ Samudera Cabang Merak. Utilizing a descriptive and verificative approach, the research employs Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to examine the causal relationships between independent and dependent variables. The study analyzes secondary time-series data sourced from the company's internal financial reports for the period 2019–2023. Comprehensive evaluations of the measurement model (Outer Model) and structural model (Inner Model) were conducted to ensure validity, reliability, and data robustness. The results indicate that the model possesses strong predictive power, with a coefficient of determination () of 0.717, meaning that 71.7% of the variation in company revenue can be explained by fleet growth and related operational factors. Hypothesis testing confirms that fleet growth has a positive and significant impact on revenue. These findings provide empirical evidence that fleet expansion strategies are effective determinants in maximizing the financial performance of shipping agency companies